2015
DOI: 10.1007/s11302-015-9488-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA uc.48+ is involved in diabetic neuropathic pain mediated by the P2X3 receptor in the dorsal root ganglia

Abstract: Some long non-coding RNAs (lncRNAs) participate in physiological processes that maintain cellular and tissue homeostasis, and thus, the dysregulated expression of lncRNAs is involved in the onset and progression of many pathological conditions. Research has indicated that the genetic knockout of some lncRNAs in mice resulted in peri-or postnatal lethality or developmental defects. Diabetes mellitus (DM) is a major cause of peripheral neuropathy. Our studies showed that the expression levels of lncRNA uc.48+ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 56 publications
0
99
0
Order By: Relevance
“…**p < 0.01 compared to the control group; ## p < 0.01 compared to the DM group and STZ-induced mechanical allodynia is mediated by P2X3 receptors in the DRG neurons [20]. DNP is a common complication of T2DM [3,26,[30][31][32]. Our results showed that thermal hyperalgesia and abnormal mechanical hyperalgesia in DM rats were increased compared with those in control rats.…”
Section: Discussionmentioning
confidence: 51%
“…**p < 0.01 compared to the control group; ## p < 0.01 compared to the DM group and STZ-induced mechanical allodynia is mediated by P2X3 receptors in the DRG neurons [20]. DNP is a common complication of T2DM [3,26,[30][31][32]. Our results showed that thermal hyperalgesia and abnormal mechanical hyperalgesia in DM rats were increased compared with those in control rats.…”
Section: Discussionmentioning
confidence: 51%
“…It has been suggested that lip inflammation leads to increased P2X 3 receptors expression in TRG mediated by calcitonin gene-related peptide and could be involved in ectopic mechanical allodynia (31). In addition, some previous studies have determined enhanced P2X 3 receptors expression in dorsal root ganglion (DRG) after muscle inflammation (32). However, some studies claim that P2X 3 -expressing TRG neurons considerably differ from DRG afferent neurons, suggesting differences in pain transmission depending on the location of pain occurrence, and that the underlying mechanisms of pain originating from different body regions are unique (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that these ncRNAs are emerging key regulators of gene expression under physiological and pathological conditions (Wang and Chang, 2011; Yang et al, 2014; Li et al, 2016). Moreover, emerging data have shown that ncRNAs are of crucial importance in various types of pain, particularly NP (Chen et al, 2014; Shao et al, 2015; Zhang and Banerjee, 2015; Wang et al, 2016). However, the regulatory functions of ncRNAs in NP and their underlying functional mechanisms have not been systematically described.…”
Section: Introductionmentioning
confidence: 99%